APPLICATION OF TUTOR METHODS IN THE FULLEST TESTING OF TEACHER PERFORMANCE MEASUREMENT - Halimatussakdiah Halimatussakdiah (Universitas Negeri Medan, 2017)
Abstract: Implementation of Peer Tutor Method In Fulfilling Performance Assessment of Teacher. Initial analysis in 2017 to 36 teachers at SDN Kecamatan Deli Tua found the problem that teachers have not fulfill the teacher performance requirement as required by MENPAN and RB No.16 Year 2009 which are: pedagogic competence, personality competence, social competence, and competence professional. Fulfillment of PKG by applying peer tutor method strategy that can improve teacher competence (pedagogik, personality, social and professional). This research method is descriptive qualitative. Locations in SDN. 101801 and SDN 108075 Deli Tua District Deli Serdang District. The study was conducted from June to November 2017 at SDN. 101801 and SDN. 108075 Deli Tua Sub-district Deli Serdang Regency. Based on the results of research, found that of 36 teachers there are 7 people (19.44%) in good category, 12 people (33.33%) in enough category, 9 people (25%) on medium category, 8 people (22,22%) in less category. Furthermore, the average teacher competence of 65.23 is in the enough category, thus the application of peer tutor method can improve the Performance Assessment of Elementary Teacher Performance. Keywords: Method, Peer Tutor, Fulfillment, PKG, SD Abstrak: Penerapan Metode Tutor Sebaya Dalam Pemenuhan Penilaian Kinerja Guru SD. Analisis awal pada 2017 terhadap 36 orang guru di SDN Kecamatan Deli Tua ditemukan permasalahan bahwa guru belum memenuhi butir-butir kinerja guru yang disyaratkan sesuai dengan Peraturan MENPAN dan RB No.16 Tahun 2009. yaitu: Kompetensi pedagogik, Kompetensi kepribadian, Kompetensi sosial, dan Kompetensi professional. Pemenuhan PKG dengan menerapkan metode tutor sebayamerupakan strategi yang dapat meningkatkan kompetensi guru (pedagogik, kepribadian, sosial dan professional). Metode penelitian ini deskriptif kualitatif. Lokasi di SDN. 101801 dan SDN 108075 Kecamatan Deli Tua Kabupaten Deli Serdang. Penelitian ini dilaksanakan dari Juni s.d November 2017 di SDN. 101801 dan SDN. 108075 Kecamatan Deli Tua Kabupaten Deli Serdang. Berdasarkan hasil penelitian, ditemukan bahwa dari 36 orang guru terdapat 7 orang (19,44%) pada kategori baik, 12 orang (33,33%) cukup, 9 orang (25%) sedang, 8 orang (22,22%) pada kurang. Selanjutnya rata-rata kompetensi guru yaitu 65,23 yaitu kategori Cukup, dengan demikian Penerapan metode tutor sebaya dapat meningkatkan Pemenuhan Penilaian Kinerja Guru SD. Kata Kunci: Metode, Tutor Sebaya, Pemenuhan, PKG, SD